2019
DOI: 10.1002/aic.16897
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic curli enables efficient microbial electrocatalysis with stainless‐steel electrode

Abstract: Microbial electrocatalysis systems (MES) provide a cutting‐edge solution to global problems associated with the environment and energy, but practical applications are hindered by the expensive electrode materials. Although stainless steel (SS) has been proposed as a promising inexpensive candidate, poor cell/SS interaction results in a low performance for MES. Here, a new synthetic biology approach was established for reinforcing the cell/SS interaction. Hybridized curli nanofibers fused with a metal‐binding d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…For microbial CO 2 transformation to formic acid, formate dehydrogenase was usually responsible for the catalytic conversion, where intracellular NAD(P)H served as the electron donor 33,34 . It was reported that S. loihica PV‐4 contained the formate dehydrogenase and had high catalytic activity in the cathode of MEC 4,19 . It was speculated that S. loihica PV‐4 could transform CO 2 to formic acid with the extracellular cathodic electron donor (Figure S8).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For microbial CO 2 transformation to formic acid, formate dehydrogenase was usually responsible for the catalytic conversion, where intracellular NAD(P)H served as the electron donor 33,34 . It was reported that S. loihica PV‐4 contained the formate dehydrogenase and had high catalytic activity in the cathode of MEC 4,19 . It was speculated that S. loihica PV‐4 could transform CO 2 to formic acid with the extracellular cathodic electron donor (Figure S8).…”
Section: Resultsmentioning
confidence: 99%
“…The MECs system was constructed in a dual‐chamber bioelectrochemical system, where the CO 2 reduction was carried out in the cathodic chamber as described in previous reports 21 . The anodic chamber of the MECs was filled with 50 mM NaCl and 1 mM H 2 SO 4 , while the cathodic chamber was added with 5 mM bicarbonate (the source of CO 2 ) and cell suspension (OD600 = 1.0) in 50 mM hydroxyethyl piperazineethanesulfonic acid buffer solution (HEPES, pH = 7.0) 19 . Carbon felt (2 cm × 3 cm) was used as the anodic electrode, while CC or BW (1 cm × 2 cm) was used as the cathodic electrode.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior efforts to direct electroactive biofilm formation on surfaces have focused solely on engineering cell-electrode attachment, rather than patterning, through synthetic biology and materials engineering strategies. These works were based on either (I) enhancing biofilm formation by expressing adhesive appendages on cell surfaces 49,50 and increasing c-di-GMP levels 51,52 or (II) placing complementary chemical or DNA-based structures on substrates and cell surfaces to bond cells to electrodes [53][54][55][56][57] . Compared with these previous works, our strategy does not require electrode pretreatment for electroactive biofilm patterning and can generate robust biofilms with defined dimensions.…”
Section: Discussionmentioning
confidence: 99%